Brain Abscess: A Rare Clinical Case with Oral Etiology. (4th January 2022) - Pereira, André João da Silva Pais Rocha; Tavares, Ana Teresa; Prates, Marcelo; Ribeiro, Natacha; Fonseca, Luís Filipe; Marques, Maria do Rosário; Proença, Francisco
Abstract : Brain abscess is a very rare condition but has a significant mortality rate. The three main routes of inoculation are trauma, contiguous focus, and the hematogenous route. The odontogenic focus is infrequent and is usually a diagnosis of exclusion. This paper presents a brain abscess case proven to be of dental origin, caused by Actinomyces meyeri and Fusobacterium nucleatum . This case highlights the risk underlying untreated dental disease and why oral infectious foci removal and good oral health are essential in primary care.